2015
DOI: 10.1186/s40066-015-0038-0
|View full text |Cite
|
Sign up to set email alerts
|

Soil fertility status and wheat nutrient content in Vertisol cropping systems of central highlands of Ethiopia

Abstract: Background: Land degradation reduces agricultural productivity and poses a serious threat on food security status of households. In Ethiopia, farmers have been using only urea and di-ammonium phosphate for more than 15 years. Several reports that indicate lack of response to these fertilizers, which could be due to limitation of nutrients other than nitrogen and phosphorus. Therefore, the present study was initiated to evaluate the soil fertility status of ten sites in central highlands Vertisols of Ethiopia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

22
73
3
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(99 citation statements)
references
References 28 publications
22
73
3
1
Order By: Relevance
“…Based on the rating developed for those nutrients it were found to be above the optimum range (Berhanu, 1985;Hazelton and Murphy, 2007). This result is also in agreement with former findings in different vertisols dominated areas of Ethiopia (Desta, 1982;Fassil and Charles, 2009;Hailu et al, 2015;Kamara et al, 1989;Lemma and Smit, 2008).…”
Section: Soil Propertysupporting
confidence: 93%
See 1 more Smart Citation
“…Based on the rating developed for those nutrients it were found to be above the optimum range (Berhanu, 1985;Hazelton and Murphy, 2007). This result is also in agreement with former findings in different vertisols dominated areas of Ethiopia (Desta, 1982;Fassil and Charles, 2009;Hailu et al, 2015;Kamara et al, 1989;Lemma and Smit, 2008).…”
Section: Soil Propertysupporting
confidence: 93%
“…The low S was also expected because the experimental soil had low organic matter content (source of about 95% of S) indicating that it's potential to supply S to plant growth through mineralization is low. Other authors also reported deficiency in S in Vertisols of Ethiopia (EthioSIS, 2016;Fanuel, 2015;Habtamu et al, 2014;Hailu et al, 2015;Lelago et al, 2016).…”
Section: Soil Propertymentioning
confidence: 93%
“…Although many efforts have been made to develop high-yielding variety of wheat in Ethiopia, the productivity of wheat is still far below the potential yield reported elsewhere as a result of soil quality depletion and low soil fertility (Harden 2001;Lal 2001). The deficiency of some micronutrient besides widespread N and P (and localized K) deficiencies in major wheat-growing areas of Ethiopian has been recently reported (Hailu et al 2015). These problems are aggravated by continuous nutrient depletion due to the complete harvest of whole plant biomass and losses in runoff and soil erosion (Vlek 1993;Sanchez et al 1997), which have led to negative nutrient balances (Stoorvogel and Smaling 1990).…”
Section: Introductionmentioning
confidence: 97%
“…The results from both of these initiatives showed deficiency of 3 to 6 nutrients N, P, S, Zn, Mo and B. in most parts of the country and crops responded to the application of additional nutrient. Moreover, the plant analysis data from the same sites indicated that wheat plants were deficient in N, P, Zn and K (Hailu et al, 2015).…”
mentioning
confidence: 97%